Analisis Pelaksanaan Prosedur Pengeluaran Kas pada Dinas Sosial Kota Magelang - Renaldo Renaldo; Suci Nasehati Sunaningsih (Jurnal Syntax Transformation, 2021)
Cash disbursement to the government is a very important component in implementing the planned development program. The government's cash disbursement department has systems and procedures that control cash disbursements. The purpose of this study was to determine whether the cash disbursement system and procedures were in accordance with existing regulations. The object of this research is the Social Service of Magelang City. The analytical method used is descriptive qualitative analysis method which aims to create a systematic, factual, and factual description, by comparing the system and cost procedures carried out by the Magelang City Social Service with the concept of a cash disbursement system. The results of the study show that the cash disbursement procedure at the Magelang City Social Service is in accordance with the existing rules, namely the Magelang City government regulation number 73 of 2017.Based on the results of research and discussions conducted at the Magelang City Social Service, it can be concluded that the cash disbursement procedure Spending Inventory Money (UP)/Change Money (GU)/Add Money (TU)/Directly (LS) at the Magelang City Social Service has been effective and in accordance with applicable regulations, namely Magelang Mayor Regulation Number 63 of 2018 concerning amendments to Mayor Regulation Number 73 Year 2017 concerning Systems and Procedures for Administration of Regional Financial Expenditures